Implementasi Pelatihan Kerja Pada PT. Mulia Glass Float Division 3 Cikarang - Mohamad Siswanto; Dedi Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to carry out job training activities or on job training at PT. MuliaGlass is a form of company attention to employees which is measured through performance, communication, and complaint handling. productivity and employee loyalty are expected to increase by managing these three dimensions. This method uses a qualitative method, namely by observing the scope of the company by direct observation and interviews with employees, paying attention to how processes occur within the company. Then the results of this study indicate that the results show that PT. Mulia Glass Float Division 3 Cikarang has a structured and planned job training program. The company realizes the importance of developing employees through training to improve product quality and production efficiency. Job training is carried out regularly by involving competent instructors and using training methods that suit the needs of employees. Then the commitment and handling of PT. MuliaGlass has a positive influence on improving performance.